Extracellular vesicles derived from antigen-presenting cells pulsed with foot and mouth virus vaccine-antigens act as carriers of viral proteins and stimulate B cell response - Menay, Florencia (2024)
Foot and mouth disease (FMD) is a highly contagious infection caused by FMD-virus (FMDV) that affects livestock worldwide with significant economic impact. The main strategy for the control is vaccination with FMDV chemically inactivated with binary ethylenimine (FMDVi). In FMDV infection and vaccination, B cell response plays a major role by providing neutralizing/protective antibodies in animal models and natural hosts. Extracellular vesicles (EVs) and small EVs (sEVs) such as exosomes are important in cellular communication. EVs secreted by antigen-presenting cells (APC) like dendritic cells (DCs) participate in the activation of B and T cells through the presentation of native antigen membrane-associated to B cells or by transferring MHC-peptide complexes to T cells and even complete antigens from DCs. In this study, we demonstrate for the first time that APC activated with the FMDVi O1 Campos vaccine-antigens secrete EVs expressing viral proteins/peptides that could stimulate FMDV-specific immune response. The secretion of EVs-FMDVi is a time-dependent process and can only be isolated within the first 24 h post-activation. These vesicles express classical EVs markers (CD9, CD81, and CD63), along with immunoregulatory molecules (MHC-II and CD86). With an average size of 155 nm, they belong to the category of EVs. Studies conducted in vitro have demonstrated that EVs-FMDVi express antigens that can stimulate a specific B cell response against FMDV, including both marginal zone B cells (MZB) and follicular B cells (FoB). These vesicles can also indirectly or directly affect T cells, indicating that they express both B and T epitopes. Additionally, lymphocyte expansion induced by EVs-FMDVi is greater in splenocytes that have previously encountered viral antigens in vivo. The present study sheds light on the role of EVs derived from APC in regulating the adaptive immunity against FMDV. This novel insight contributes to our current understanding of the immune mechanisms triggered by APC during the antiviral immune response. Furthermore, these findings may have practical implications for the development of new vaccine platforms, providing a rational basis for the design of more effective vaccines against FMDV and other viral diseases.